1992
DOI: 10.1136/jnnp.55.4.308
|View full text |Cite
|
Sign up to set email alerts
|

Platelet catecholamines in cluster headache.

Abstract: Platelet tyrosine and catecholamine (CA) content was measured in cluster headache sufferers during the different phases of the illness. Compared with controls, cluster headache sufferers had lower platelet levels of norepinephrine (NE) and epinephrine (E) in all phases of the syndrome. Tyrosine levels were increased significantly during the cluster headache attack. We suggest that these results provide biochemical evidence of sympathetic nervous system (SNS) hypofimction in cluster headache. Norepinephrine and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…The reduced catabolic activity of this enzyme could explain the increased DA levels in platelets. The low level of norepinephrine—produced by DBH activity using DA as substrate—reported in those with migraine at menses, 15,33 together with an altered allelic distribution of the DBH gene found in migraine patients, 7 supports this hypothesis. No data are available on DBH activity in CH.…”
Section: Commentsmentioning
confidence: 87%
“…The reduced catabolic activity of this enzyme could explain the increased DA levels in platelets. The low level of norepinephrine—produced by DBH activity using DA as substrate—reported in those with migraine at menses, 15,33 together with an altered allelic distribution of the DBH gene found in migraine patients, 7 supports this hypothesis. No data are available on DBH activity in CH.…”
Section: Commentsmentioning
confidence: 87%
“…In ECH patients, plasma levels of TYRA, other elusive amines, and DA are significantly elevated in both the remission and active periods. One possibility is that this may reflect a biochemical shift of TYR metabolism involving, on the one hand, an increase in the activity of the TYR decarboxylase enzyme that transforms TYR into TYRA and l ‐DOPA into DA and, on the other hand, a decrease in the activity of TYR hydroxylase that results in a decrease in the synthesis of NE, as observed in platelets and cerebral spinal fluid of CH sufferers . In addition, the observation that NE levels are low in all phases of ECH suggests that this alteration may reflect an ongoing sympathetic dysfunction, since TYR hydroxylase is present in this system…”
Section: Discussionmentioning
confidence: 99%
“…The nature of the hypothalamic dysfunction and its role in the pathogenesis of CH is unknown. Studies have demonstrated that the levels of DA and TA, Oct and Syn are very high in plasma and platelets of CH patients in remission and active periods, whereas those of NE are significantly lower than those of control individuals (2,3,13). We suggested that if the same biochemical abnormalities are present in the hypothalamus and other centers of the pain matrix, these biochemical anomalies may be involved in the pathogenesis of episodic CH (2).…”
Section: Introductionmentioning
confidence: 99%